Expression of Matrix Metalloproteinases and Their Tissue Inhibitors in Human Brain Tumors - Lampert, Klaus (American Society for Investigative Pathology, 1998)
In this study, we investigated the expression patterns of 15 matrix metalloproteinases (MMPs) and three tissue inhibitors of metalloproteinase in gliomas, medulloblastomas, and normal brain tissue. By Northern blot analysis we found increased levels of mRNAs encoding for gelatinase A, gelatinase B, two membrane-type MMPs (mt1- and mt2-MMP), and tissue inhibitors of metalloproteinase-1 in glioblastomas and medulloblastomas. We observed a significant increase of mt1-MMP, gelatinase A, gelatinase B, and tissue inhibitors of metalloproteinase-1 in glioblastomas as compared with low-grade astrocytomas, anaplastic astrocytomas, and normal brain. In medulloblastomas, the expression of mt1-MMP, mt2-MMP, and gelatinase A were also increased, but to a lesser extent than that observed in glioblastomas. These data were confirmed at the protein level by immunostaining analysis. Moreover, substrate gel electrophoresis showed that the activated forms of gelatinases A and B were present in glioblastomas and medulloblastomas. These results suggest that increased expression of mt1-MMP/gelatinase A is closely related to the malignant progression observed in gliomas. Furthermore, the present study demonstrates, to our knowledge for the first time, that medulloblastomas express high levels of MMP.